Long-term follow-up of severely symptomatic women with adenomyoma treated with combination therapy - Wei-Min Liu; Ching-Hui Chen; Li-Hsuan Chiu; Chii-Ruey Tzeng (Elsevier, 2013)
Objective: The aim of our study was to assess the long-term efficacy of conservative surgery combined with gonadotropin-releasing hormone agonist therapy for uterine adenomyoma. Materials and Methods: We carried out an uncontrolled descriptive study of 285 women who had symptomatic uterine adenomyoma. A total of 186 women with pathologically proven adenomyoma underwent ultramini-laparoscopic adenomyomectomy and a 6-month course of goserelin acetate treatment, and were evaluated semi-annually during a follow-up period of at least 3 years. Results: Patient scores for dysmenorrhea using a self-reported six-point verbal numeric rating scale significantly declined compared with the baseline assessment, from 3.84 ± 0.65 to 0.33 ± 0.57, 0.52 ± 0.86, and 0.88 ± 1.29 at the end of the 1-, 2-, and 3-year follow-up visits, respectively (p < 0.001). Similar reductions were observed for analgesic usage scores. Menorrhagia scores significantly decreased compared with the baseline assessment, from 3.45 ± 1.46 to 0.42 ± 0.59, 0.65 ± 0.83, and 1.1 ± 1.34 at the end of the 1-, 2-, and 3-year follow-up visits, respectively (p < 0.001). Conclusion: Combination therapy for adenomyoma provides an effective treatment option for long-term symptom control and uterine preservation in severely symptomatic women for whom previous long-term drug therapy has failed or proven to be intolerable.